Violent rituals of the Hebrew Bible - Olyan, Saul M. 1959- (Oxford Oxford University Press USA - OSO, 2019)
Although seldom studied by biblical scholars as a discrete phenomenon, ritual violence is mentioned frequently in biblical texts. Violent Rituals of the Hebrew Bible is the first book to investigate violent rites, the ritual settings in which they occur, their various literary contexts, and the identity and aims of their agents in order to speak in an informed way about the contours and social aspects of ritual violence as it is represented in the Hebrew Bible.
Cover -- Violent Rituals of the Hebrew Bible -- Copyright -- Dedication -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction -- 1. Ritual Violence Prescribed -- 2. Violent Rites Narrated -- 3. Ritual Violence Envisioned -- 4. Ritual Inversion and Mitigating Rites as Components of Ritual Violence -- 5. The Role of Circumstantially Dependent Rites in Ritual Violence -- 6. The Social Dimensions of Ritual Violence -- Conclusion -- Notes -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Old Testament-Criticism, interpretation, etc; Violence in the Bible; Ritual-Biblical teaching; Electronic books